2016
DOI: 10.1007/978-3-319-27356-3_4
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Feeding Behaviour in the Assessment of Animal Welfare

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 124 publications
0
10
0
Order By: Relevance
“…The linear tendency in the frequency of visits to the feeder showed that the greater the inclusion of molasses, the greater the number of times the animals tend to go to the feeder. The greater fractionation of intake throughout the day is desirable, as it is related to greater health and better welfare in animals ( Nielsen et al, 2016 ). This tendency can also be related to the rapid fermentation and production of fatty acids in the rumen promoted by sugars ( Martel et al 2011 ; Soder et al, 2011 ) contained in SBM, quickly increasing the osmotic pressure and concentration of fatty acids in the rumen, causing that animals reach “brain regulation of satiety” earlier, thus leading to greater fractionation of intake as a measure to prevent metabolic disorders ( Ginane et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The linear tendency in the frequency of visits to the feeder showed that the greater the inclusion of molasses, the greater the number of times the animals tend to go to the feeder. The greater fractionation of intake throughout the day is desirable, as it is related to greater health and better welfare in animals ( Nielsen et al, 2016 ). This tendency can also be related to the rapid fermentation and production of fatty acids in the rumen promoted by sugars ( Martel et al 2011 ; Soder et al, 2011 ) contained in SBM, quickly increasing the osmotic pressure and concentration of fatty acids in the rumen, causing that animals reach “brain regulation of satiety” earlier, thus leading to greater fractionation of intake as a measure to prevent metabolic disorders ( Ginane et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another typical trait characterizing the natural feeding behavior of cattle is synchronization ( 8 , 48 ). In housed cattle, the strong desire of the animals to access the manger as a group may lead to feed competition with negative health effects for individual animals ( 49 ). Feed competition may reduce the average meal duration of cattle and dominant animals with ad libitum access to feed may eat a larger amount of dry matter than subordinate individuals ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…A shorter-term measure of feeding was required for our protocol; consequently, the number of troughs, the amount of feed available and cleanliness of feed troughs were included. The reviewed protocols do not include an animal-based measure to quantify feed intake; therefore, we developed a measure described as Feed Behaviour Score, because feeding behaviour is particularly important as it is informative about the immediate level of hunger, social competition for feed [41], and appetitive response to climatic challenges [42][43][44]. The Welfare Quality ® protocol contains additional measures for water provision, including water availability and cleanliness.…”
Section: Good Feedingmentioning
confidence: 99%